The concept of receiving in modern Arabic criticism - الشواف نجات (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
This research presents a theoretical study of the term Reception in an attempt to study the term’s problematic issue , and to shed light on the most important issues raised by this term or as it was later defined as a theory . The most important one of these issues is to deal with the literary text as a subject and not a language , and to show interest in literary issues and to deal with the text as one block and a multi-reading one or open to multiple readings . Thus the research was based on identifying the cognitive principles of Reception theory , the name which was related with the German school Konstanz . These principles helped the Reception theory to understand the relation which combines the recipient and the social conditions in which the reception takes place. As a result , the study mentioned the Reception theory pioneers and the terms they come up with and on the top of them ( Jauss) : who specifies the horizon expectation term and the aesthetic distance term . Wolfgang Iser, like (Jauss) , emphasized the interest in the relationship between the text and the reader . The most important concepts he set are: the interaction between the text and the reader, the gaps and the implicit reader term. In addition to studying Reception trends in modern criticism, starting with the authority of the author, then the authority of the text, finally, the authority of the reader. This has been most practiced with Reception critics. As their theory of Reception restored the reader’s rights and importance after they had been forgotten in the classical theories of literature.